Effect of Deformation Parameters on Microstructure and Mechanical Properties of Internal Crack Healing in As-Cast 30Cr2Ni4MoV Steel - Yongxing Jiao; Cunlong Zhou; Jiansheng Liu; Xuezhong Zhang (Advances in Materials Science and Engineering)
Crack defects seriously affected the quality of heavy forgings, which needed to be eliminated by forging process. In this study, the healing process of internal crack defects was studied under different deformation parameters. The internal crack was produced by drilling the sample of 30Cr2Ni4MoV steel and then compressing the sample with different deformation. The microstructure of the crack healing zone was observed using an optical microscope. Meanwhile, the static and dynamic mechanical properties of the crack healing zone were tested by room-temperature tensile tests and impact tests, respectively. The results showed that dynamic recrystallization (DRX) and grain growth were the main factors for internal crack healing. When the forging ratio (FR) was 1.5, the cracks at the corner of the void began to heal, which was caused by DRX. At FR 2.0, the DRX was completed and the center crack was completely healed. The tensile properties of crack healing zones were restored to more than 95% of the base material. As the FR increased to 2.2, the elongation increased slightly and the yield strength decreased slightly, which indicated that the grain growth played an important role in the plastic recovery and DRX played an important role in strength recovery. The dynamic mechanical properties of the crack healing zone gradually increased with the increase of deformation. Furthermore, the maximum value of impact toughness reached FR 2.0, and the recovery rate of impact toughness was above 96%. When the deformation continues to increase, the grains grew up after DRX, which made the impact energy decrease.